Enabling Employability Through International Mobility (Comparative & International Education Series, 2022)
To ensure our graduates are globally enabled, international experiences in different cultural contexts are essential. Such experiences enhance soft skills such as resilience, teamwork and communication that support students to build diverse professional networks and increase employment opportunities. Through a capstone work integrated learning (WIL) subject in occupational therapy, international placements were created from 2016 with two partner organisations in India and Vietnam. Each year students complete a 10-week international placement in India or Vietnam working with local project supervisors. Participating in this program assisted student employability, with the majority of students reporting that their WIL experience helped them secure a job within the first few weeks after completion of their occupational therapy degree. This chapter presents student experiences in the Global South and demonstrates how WIL helped develop students’ global citizenship and enhanced their employability.